Enraizamento de microestacas e miniestacas de mamoeiro híbrido UENF/CALIMAN 02 - Oliveira, Márcio José Vieira de (2014)
The development of techniques of micropropagation of papaya through tissue culture stands as a "tool" of wide application in large-scale production of clones with superior characteristics, the sexes defined and free of viruses. In micropropagation, the po